Pelatihan Pembuatan Pupuk Organik Cair dari Limbah Organik untuk Mewujudkan Pertanian Berkelanjutan di Desa Blungun - Annisa Nisrina Rosada; S. Agus Santoso; Maghfira Amadea Kiswara; Adam Sribakti Kusuma Wangsa; Febriyati Esmi Sumilir; Quin Qonita Ruhul Jadidah; Danialin Siswo Handoyo; Alfons Valentino; Bagas Dwi Prasetyo; Vincencius Martiano Christ Setyanto (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Liquid organic fertilizer is a fertilizer whose basic ingredients come from animals or plants that have undergone fermentation, and the product is in liquid form. Training on making liquid organic fertilizer (POC) by utilizing household organic waste and agricultural waste was carried out in Blungun Village, Jepon District, Blora Regency, on August 4, 2025. The purpose of this research is to increase the awareness and skills of the Blulung Village community in utilizing organic waste as a basic material for making liquid organic fertilizer (POC). The training method used by the community service team for the community service partners was carried out through several methods, namely the compaction method and question and answer. Through training activities, it is hoped that it can increase the participants' understanding of how to turn unused organic waste into something valuable.